Marketing Strategy Agility and MSME Resilience: Navigating Post-Digital Consumption Behavior Shifts for Sustainable Economic Impact - Widya Nengsih; Ratnawita Ratnawita; Selfiana Selfiana (Dinasti International Journal of Education Management and Social Science, 2026)
Changes in post-digitalization consumption behavior encourage Micro, Small, and Medium Enterprises (MSMEs) to adapt marketing strategies that are more flexible and responsive to market dynamics. This study aims to analyze the influence of marketing strategy agility on the resilience of MSMEs in facing shifts in digital consumer behavior and its implications for economic sustainability. This study is located on MSMEs in the culinary sector in Cirebon City, Indonesia. The research uses a quantitative approach with a survey method of 60 MSME actors who have utilized digital media in marketing activities. The data analysis technique used multiple linear regression. The results of the study show that marketing strategy agility has a positive and significant effect on the resilience of MSMEs. The ability to adapt to market trends, strategic flexibility, and digital channel optimization have been proven to improve the ability of MSMEs to maintain business performance amid changes in consumer behavior. In addition, shifts in digital consumption behavior, particularly preferences for ease of access and speed of services, are contextual factors that reinforce the relevance of adaptive marketing strategies. This research contributes to the development of marketing management studies, especially related to the role of agility in the context of MSMEs, as well as practical implications for business actors and policymakers in strengthening economic resilience based on digital transformation.